Respiratory and Pulmonary Function Problems among Flour Mills Workers in East of Iran - Teimori, Gholamheidar (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Aim: Flour dust is one of the allergens dust in the workplaces, and its occupational exposure can cause respiratory impairments. The aim of this study was to investigate respiratory and pulmonary function problems in flour mills workers exposure to flour dust. Materials and Methods: This cross-sectional study was carried out at 11 flour-producing factories in Iran. Study subjects were including to 286 males (176 male workers with current exposure to flour dust and 110 male unexposed employees). Determination of dust concentration was carried out with personal dust sampler at all production wards of studied industries. Respiratory symptoms were investigated with American Thoracic Society questionnaire. Lung function tests were done by a calibrated spirometer. The statistical analysis was performed by SPSS 18 software and t-test, Chi-square, linear, and logistic regressions. Results: Age and job tenure means of exposed group were 35.2 ± 8.6 and 11.9 ± 6.03 years, respectively. This result, for unexposed group, too was gained 35.3 ± 8.5 and 10.89 ± 6.5 years, respectively. Atmospheric concentrations of respirable and inhalable dust were 12.4 ± 2.41 and 33.26 ± 3.47 mg/m3, respectively. These results indicated that prevalence of respiratory symptoms in exposed subjects was significantly higher than non-exposed workers. Likewise, pulmonary function parameters were significantly lower in exposed than the reference group. Conclusions: The findings of this study showed that occupational exposure to flour dust could be a significant factor of the prevalence of respiratory symptoms and functional disorders of the pulmonary.